Keunggulan Pembelajaran Seni Baca Al-Qur’an di Pondok Pesantren Nurul Falah Airmesu Timur - Eko Maulana (EDOIS: Journal of Islamic Education, 2023)
The art of reading the Koran is less attractive because the learning medium used by the teacher concerned does not match the love of students; as a result, this learning cannot achieve maximum results. Therefore, every teacher needs to have interesting tricks and styles in every lesson that is carried out, and it is very important to understand and adjust to the tastes or interests of the students based on their era, namely millennials, who are characterized by the function of technology in all aspects, including learning media, which should be technology-based. The research method carried out on the case study above is to take a participatory approach (action research) to the instructor who is directly related to the problem, and the results show a clear perspective based on the fact that it is very important to have an appropriate and interesting learning medium for every teacher, especially in the art of reading the Qur'an; otherwise, the learning results cannot be maximized according to the target expected in every school. The method of reading the Qur'an with an interesting art or style can significantly affect the interest in learning of each student, which is the key to success for students, especially in the group of readers of the Qur'an. Besides that, it will make the work of each teacher easier and maximized, as well as students following the lessons with relaxed happiness and full of enthusiasm. In this case, it is necessary to have productive and good cooperation between the management of the institution, the teachers as teaching staff as well as educators, and it is also necessary to have closeness between all parties to students who are under the supervision of an Islamic Boarding School. The school supervisor always conducts monitoring on the course of learning, ensuring the achievement of student learning outcomes, as has become the hope of the institution based on the vision and mission of the Nurul Falah Airmesu Islamic Boarding School.